تحسين أداء المؤسسة في ظل إدارة الجودة الشاملة - مداحي محمد الأمين, لعوج محمد الإسلام (My University, 2022)
The total quality management approach is among the new methods that can be used by the economic institution, to adapt to the great challenges imposed by the nature of the current global economy and what is characterized by intense competition, technological revolution and globalization ... etc., and this approach is considered one of the most prominent administrative methods that are considered As entrances to improve institutional performance, because this approach leads to reaching the degree of excellence in performance, which is a goal that every institution wishing to excel and excel in the current global economy should strive for.
Keywords: quality،total quality management،performance